Advances in the understanding and treatment of Cutaneous T-cell Lymphoma - Bakr, Farrah S.; Whittaker, Sean J. (Frontiers in Oncology, 2022)
Cutaneous T-cell lymphomas (CTCL) are a heterogeneous group of non-Hodgkin’s lymphomas (NHL) characterised by the clonal proliferation of malignant, skin homing memory CD4+ T-cells. Recent advances have been made in understanding the molecular pathogenesis of CTCL. Multiple deep sequencing studies have revealed a complex genomic landscape with large numbers of novel single nucleotide variants (SNVs) and copy number variations (CNVs). Commonly perturbed genes include those involved in T-cell receptor signalling, T-cell proliferation, differentiation and survival, epigenetic regulators as well as genes involved in genome maintenance and DNA repair. In addition, studies in CTCL have identified a dominant UV mutational signature in contrast to systemic T-cell lymphomas and this likely contributes to the high tumour mutational burden in CTCL. As treatment options for advanced stages of CTCL are limited and associated with short-lived responses, targeting these deregulated pathways could provide novel therapeutic approaches for CTCL patients. In this review article we summarise the key pathways disrupted in CTCL and discuss the potential therapeutic implications of these findings.